Determining Program Study Using AHP with Dynamic Criterias and Weights Based on GIS-Mobile - Kurniawan, Mohammad Rizky; Kurniawati, Ayuningtyas; Saon, Sharifah (Universitas Negeri Malang, 2020)
This research aim to develop a decision support system based on GIS-Mobile Apps using Analytical Hierarchy Process (AHP) Algorithm and softmax function for dynamic weight. The stages of AHP dynamic criteria in this system is the preparation of a hierarchy, prioritization, consistency, and the weight of priority. ). The use of AHP in this system involves four criteria which keywords, department accreditation, accreditation of colleges and colleges location distance that can be set by the user dynamically. Experience Programming (XP) is model development that choosed by author for process development system. The step begin with planning, design, coding, and testing. The result of this research is a GIS-Mobile Apps to determine a list of recommended program study with the greatest weight from user input criteria.